Sign Language and Culture: Understanding Communication in the Deaf Community - Muhammad Nur Iman (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This study explores the relationship between sign language and culture within the Deaf community. Sign language is not only a means of communication but also a reflection of the cultural identity and values held by Deaf individuals. Through qualitative analysis of various forms of communication within this community, the research reveals how sign language serves as a medium for expressing unique experiences, traditions, and social norms. The study also discusses the role of sign language in fostering solidarity and collective identity among community members, as well as the challenges faced in interactions with the hearing society. By examining linguistic and cultural aspects, this research aims to enhance understanding of communication within the Deaf community and highlight the importance of recognizing and valuing sign language as an integral part of cultural heritage. The findings are expected to provide deeper insights into the dynamics of communication and social interaction in diverse cultural contexts.